Exergy-Based Aerothermodynamic Evaluation of a Turbocharger Turbine Under Pulsating Flow: An Experimental Power-Based Approach - Sina Kazemi Bakhshmand; Clemens Biet (Energies)
This experimental study investigates the aerothermodynamic performance of a turbocharger turbine under steady and pulsating flow conditions across various turbine inlet temperatures (TITs) and pulsation frequencies. A power-based approach was implemented to quantify turbine heat transfer for diabatic scenarios over a range of operating turbocharger speeds. The results reveal that higher TITs significantly increase heat transfer under steady flow, driven by enhanced thermal gradients; while pulsating flow amplifies heat transfer by up to 63.6% due to intensified turbulence and frequent boundary layer disruptions. The exergy analysis shows that pulsating flow increases exergy destruction compared to steady flow, primarily due to pressure and velocity fluctuations that intensify flow friction and turbulence. At higher pulsation frequencies, exergy destruction decreases slightly, while heat transfer exergy loss becomes more prominent, reflecting a shift in the exergy balance. These higher frequencies, representative of real engine conditions, drive the flow toward quasi-steady behavior, further shaping the aerothermodynamic performance of the turbine. These findings provide valuable insights into the effects of pulsating flow on turbine heat transfer and exergy losses, offering practical implications for optimizing turbocharger turbine performance under realistic operating conditions.